A structured comparison and reflection on international position statements and professional guidance for the management of periviable infants - Peterson, J.; Southwood, G.; Smith, D. M.; Johnstone, E. D.; Mahaveer, A. (Frontiers in Pediatrics, 2025)
BackgroundSurvival rates and clinical approach to periviable infants are rapidly evolving at certain centres, but there remains variation in definition, approach and management of these infants worldwide. This review aims to narratively review and discuss professional guidelines, position statements and frameworks for management of periviable infants (22 + 0–25 + 0 weeks gestation) born in countries with the highest relative spending on healthcare.MethodsEligible countries were determined using the Organisation for Economic Co-operation and Development database. The top 10 countries with highest spend on healthcare as a proportion of their gross domestic profit were selected. A comprehensive search of relevant databases and search engines (MEDLINE, Embase, CINAHL, PsycINFO, Google Scholar) was performed to identify professional guidance documents for each eligible country. The primary outcome was the delivery room management recommendation (survival-focused or end of life care). The secondary outcomes were survival rates, disability rates and whether shared decision-making with parents was recommended.ResultsThere was variation in definition of periviable and approach to management across the 10 professional guidelines. There was a four-week difference across countries for where the limits of viability lie (22 + 0–25 + 6 weeks). At 22-weeks, eight guidelines recommended comfort care and only one country recommending active care as the default management position at birth. By 24-weeks gestation, no country recommended comfort care as the standard approach at birth.DiscussionDespite the included countries having the highest spend on healthcare as a proportion of their GDP, there is marked international variation in recommended practice in relation to the definition of and management for periviable infants. The majority of included guidelines recommended a shared decision-making approach between professionals and parents facing periviable birth, however, there were scant details about how this should be actualized and only two guidelines included decision-making aids for use with parents. The pre-birth discussion between perinatal professionals and parents facing periviable labour is complex and challenging for all involved. Further research is required to explore how best to facilitate parental understanding and involvement in these discussions to ensure parents are empowered to make the most appropriate decisions for their baby and their family.